GLT25D2 Is Critical for Inflammatory Immune Response to Promote Acetaminophen-Induced Hepatotoxicity by Autophagy Pathway - Zhang, Xiaohui; Guo, Lele; Zhang, Xiangying; Xu, Ling; Tian, Yuan; Fan, Zihao; Wei, Hongshan; Zhang, Jing; Ren, Feng (Frontiers in Pharmacology, 2020)
Acetaminophen (APAP) overdose induces hepatocyte necrosis and causes liver hepatotoxicity. Currently, the role of galactosyltransferase in APAP-induced liver injury still unclear. This study assessed the contribution of GLT25D2 gene, a kind of collagen galactosyltransferase, to the development of APAP-induced liver injury. This study found that the expression of GLT25D2 markedly increased first and then decreased in liver of mice treated with APAP, however, downregulated in liver of APAP overdose-patients compared with normal controls. Knockout of GLT25D2 significantly ameliorated the liver injury, meanwhile, downregulated the proinflammatory cytokines (IL-6, TNF-α) and chemokines (CXCL-10, MIG and CXCL-1) levels, however, and upregulated the anti-inflammatory cytokines (IL-22, IL-10) levels. Mechanistic explorations showed that (1) GLT25D2 knockout promoted autophagy pathway; and (2) the GLT25D2 knockout-induced autophagy selected to clear damaged mitochondria in APAP-induced liver injury by mitophagy; and (3) the autophagy intervention by Atg 7 siRNA cancelled liver protection by knockout of GLT25D2 through regulating liver inflammation. In conclusion, our study proves that the upregulated expression of GLT25D2 decreased autophagy to contribute to APAP-induced hepatotoxicity by mediating inflammatory immune regulatory mechanism.